CHARACTERIZATION OF THE MUCIN PHENOTYPE CAN PREDICT GASTRIC CANCER RECURRENCE AFTER ENDOSCOPIC MUCOSAL RESECTION - HONDO,Fabio Yuji (2017)
ABSTRACT BACKGROUND: Endoscopic mucosal resection is still considered an accepted treatment for early gastric cancer for selected cases. Histopathologic criteria for curative endoscopic resection are intramucosal well-differentiated adenocarcinoma, lateral and deep margins free of tumor, no histological ulceration, and no venous or lymphatic embolism. A 5% local recurrence rate has been described even when all the above-mentioned criteria are met. On the other hand, antigen expression by tumoral cells has been related to the biological behavior of several tumors. OBJECTIVE: To evaluate whether early gastric cancer mucin immunoexpression, p53 and Ki-67, can predict recurrence after endoscopic mucosal resection, even when standard histopathologic criteria for curative measures have been attempted. METHODS: Twenty-two patients with early gastric cancer were considered to have been completely resected by endoscopic mucosal resection. Local recurrence occurred in 5/22 (22.7%). Immunohistochemical study was possible in 18 (81.8%) resected specimens. Patients were divided in two groups: those with and those without local recurrence. They were compared across demographic, endoscopic, histologic data, and immunohistochemical factors for MUC2, MUC5a, CD10, p53, and Ki-67. RESULTS: Mucin immunoexpression allowed a reclassification of gastric adenocarcinoma in intestinal (10), gastric (2), mixed (4), and null phenotypes (2). Mixed phenotype (positive for both MUC2 and MUC5a) was found in 80% of cases in the local recurrence group, while the intestinal type (positive MUC2 and negative MUC5a) was found in 76.9% of cases without local recurrence (P=0.004). Other observed features did not correlate with neoplastic recurrence. CONCLUSION: The mixed phenotype of early gastric adenocarcinoma is associated with a higher probability of local recurrence after endoscopic mucosal resection.